Environmental Exposures and Mammary Gland Development: State of the Science, Public Health Implications, and Research Recommendations - Rudel, Ruthann A. (National Institute of Environmental Health Sciences, 2011)
Objectives: Perturbations in mammary gland (MG) development may increase risk for later adverse effects, including lactation impairment, gynecomastia (in males), and breast cancer. Animal studies indicate that exposure to hormonally active agents leads to this type of developmental effect and related later life susceptibilities. In this review we describe current science, public health issues, and research recommendations for evaluating MG development. Data sources: The Mammary Gland Evaluation and Risk Assessment Workshop was convened in Oakland, California, USA, 16–17 November 2009, to integrate the expertise and perspectives of scientists, risk assessors, and public health advocates. Interviews were conducted with 18 experts, and seven laboratories conducted an MG slide evaluation exercise. Workshop participants discussed effects of gestational and early life exposures to hormonally active agents on MG development, the relationship of these developmental effects to lactation and cancer, the relative sensitivity of MG and other developmental end points, the relevance of animal models to humans, and methods for evaluating MG effects. Synthesis: Normal MG development and MG carcinogenesis demonstrate temporal, morphological, and mechanistic similarities among test animal species and humans. Diverse chemicals, including many not considered primarily estrogenic, alter MG development in rodents. Inconsistent reporting methods hinder comparison across studies, and relationships between altered development and effects on lactation or carcinogenesis are still being defined. In some studies, altered MG development is the most sensitive endocrine end point. Conclusions: Early life environmental exposures can alter MG development, disrupt lactation, and increase susceptibility to breast cancer. Assessment of MG development should be incorporated in chemical test guidelines and risk assessment.